Revealing lost 16th-century royal emblems on two Andrea Amati’s violins using XRF scanning - Marie Radepont; Jean-Philippe Échard; Matthias Ockermüller; Hortense de la Codre; Oulfa Belhadj (Heritage Science, 2020)
Abstract A key issue in understanding artefacts from the past is the loss of readability of the signs they may have borne. The two 16th-century musical instruments studied here—rare Italian violins made by Andrea Amati (c.1505-1577) in Cremona—bear remains of painted heraldic emblems, which are barely legible and thus remained undeciphered until today. They are exemplary representatives of this research question, indeed combining various types of losses, which are widely encountered on archaeological artefacts: they are now incomplete (parts are missing, surfaces are abraded) and the paint matter itself, of which the signs are made, has altered. In this study, the complete original outlines and geometrical subdivisions of the shields are deduced from calculations based on the conventional heraldic construction practices of the times. Also, in situ elemental imaging of the shield areas—here using scanning X-ray fluorescence (XRF) spectroscopy— brings two types of information: (i) the nature of pigments, allowing to deduce the initial colours of the paints not discernable to the eye, whether abraded or discoloured; (ii) the spatial distribution of these pigments and colours inside the shield. This multi-approach method leads to the unprecedented revelation of a combination of symbols (tinctures of fields, emblematic ornaments, and their relative spatial distribution), all having meanings in heraldic language. The reconstructed coats of arms appear to be pointing to a very specific nine-year period (1559–1568) of the life of the queen Elisabeth (Isabel) of Valois, spouse of Philip II of Spain. We suggest that this approach, combining an imaging spectroscopic technique and a geometrical study of remaining decors, here providing new insights into the musical history at the Court of Spain, may be used to enhance the readability of a wide range of writings, signs and symbols on artefacts from the past.